Simultaneous detection and differentiation of classical Muscovy duck reovirus and goose-origin Muscovy duck reovirus by RT-qPCR assay with high-resolution melting analysis - Xu, Zhuoran; Liu, Hongwei; Zheng, Xin; Cheng, Xiaoxia; Wang, Shao; You, Guangju; Zhu, Xiaoli; Zheng, Min; Dong, Hui; Xiao, Shifeng; Zeng, Li; Zeng, Xiancheng; et al. (Frontiers in Veterinary Science, 2024)
IntroductionClassical Muscovy duck reovirus (C-MDRV) and goose-origin Muscovy duck reovirus (Go-MDRV) infections cause “Liver white-spots disease” in Muscovy duckling and gosling. It is difficult to differentiate the infections caused by C-MDRV and Go-MDRV using conventional serological methods.MethodsSpecific primers were designed and synthesized according to σNS and λA nucleotide sequences of C-MDRV and Go-MDRV, respectively. The PCR amplified products were cloned into the pMD-18-T vector. The recombinant plasmid DNA was used to establish an SYBR Green І based duplex real-time PCR assay for the simultaneous detection and differentiation of C-MDRV and Go-MDRV using high-resolution melting (HRM) analysis. The specificity, sensitivity, and repeatability of the methodology were examined based on the optimization of the reaction system and amplification conditions.ResultsC-MDRV and Go-MDRV were identified by their distinctive melting temperatures with 84.50 ± 0.25°C for C-MDRV and 87.50 ± 0.20°C for Go-MDRV, respectively. The amplifications were specific, and other non-targeted waterfowl viruses employed in this study did not show normalized melting peaks. The intra- and inter-assay coefficients of variations were between 0.05 and 1.83%, demonstrating good repeatability. The detection limits of this assay were 51.4 copies·μl−1 for C-MDRV and 61.8 copies·μl−1 for Go-MDRV, respectively. A total of 45 clinical samples were tested by RT-qPCR, with positive rates of 15.56% for C-MDRV and 22.22% for Go-MDRV, without co-infections.DiscussionThese results suggest that this duplex RT-qPCR method is highly sensitive, specific, and reproducible. The HRM assay established in this study provides a powerful tool for the differential detection and epidemiological investigation of C-MDRV and Go-MDRV.